Shakespeare and His Contemporaries - Hart, J. author. aut Link
XIII, 254 p.
Keywords: This book is concerned with language, genre, drama, and literary and historical narrative and examines the comedy of Shakespeare in the context of comedies from Italy, Spain, and France in the sixteenth and seventeenth centuries.